Twenty-Five–Year Change in Cardiac Structure and Function and Midlife Cognition: The CARDIA Study. (8th March 2022) - Rouch, Laure; Hoang, Tina; Xia, Feng; Sidney, Stephen; Lima, Joao A.C.; Yaffe, Kristine
Abstract : Background and Objective: The goal of this work was to determine whether midlife cardiac structure and function and their 25-year change from early to middle adulthood are associated with lower midlife cognition. Methods: We studied 2, 653 participants from the Coronary Artery Risk Development in Young Adults (CARDIA) study (57% women, 46% Black). Echocardiograms were obtained at year 5, 25, and 30 visits (participant mean age 30, 50, and 55 years) to assess left ventricular (LV) mass (LVM), LV systolic function with LV ejection fraction (LVEF), and LV diastolic function with left atrial volume (LAV) and early peak mitral velocity (E)/early peak mitral annular velocity (e') ratio. LVM and LAV were indexed to body surface area (LVMi and LAVi). At year 30, 5 cognitive domains were measured: global cognition, processing speed, executive function, delayed verbal memory, and verbal fluency. We investigated the association between midlife (year 30) and 25-year change in cardiac structure and function on midlife cognition using linear regressions. Results: Over 25 years, LVMi and LAVi increased with mean change (SD) per year of 0.27 (0.28) g/m 2 and 0.42 (0.15) mL/m 2, while LVEF decreased by 0.11% (0.02%). After adjustment for demographics and education, 25-year increase (≥1 SD) in LVMi was associated with lower cognition on most tests ( p ≤ 0.02); 25-year increase in LAVi was associated with lower global cognition ( p = 0.04), but 25-year decrease in LVEF was not associated with cognition. Further adjustment for cardiovascular risk factors led to similar results. In addition, unlike year 30 E/e' ratio and LVEF, higher year 30 LVMi and LAVi were significantly associated with worse cognition on most cognitive tests. Discussion: Midlife cardiac structure and its change from early to middle adulthood are associated with lower midlife cognition even after accounting for confounders. Unlike systolic function, midlife LV diastolic function and its 25-year change were also linked to cognition. Our results provide information linking early to midlife cardiac structure and function to cognition.